Pengaruh Covid-19 Dan Laba Rugi Perusahaan Terhadap Harga Saham Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Mildawati, Nonong; Erica, Denny; Mabrur Rachmah, Siti (LPPM Universitas Bina Sarana Informatika, 2023)
The type of research used is a type of statistical quantitative research. The population used in this study are all banking companies listed on the Indonesia Stock Exchange. There are 46 banking sectors listed on the Indonesia Stock Exchange. In this study, the sample was determined using the purposive sampling method with predetermined criteria so that there were 32 samples of banking sector companies listed on the Indonesia Stock Exchange, stock movements that experienced ups and downs caused by Covid-19 and shares that were still active according to the brand name during the research period, namely 2021. Data collection techniques were accessed by accessing the official website of the Indonesia Stock Exchange www.idx.co.id and the website of each company, namely share price data used were share price data. In proving and analyzing this, it is necessary to test the normality of the data and test the hypothesis. Data processing begins with Microsoft Excel and then with SPSS version 22. The results of the test (t) show that Covid-19 has an effect on the prices of banking shares listed on the Indonesia Stock Exchange and the results of the test (t) show that profit and loss has no effect on the prices of banking shares listed on the Indonesia Stock Exchange. Meanwhile, test (f) shows that Covid-19 and profit and loss together have a significant effect on the prices of banking shares listed on the Indonesia Stock Exchange.